Author Correction: FAN1 interaction with ubiquitylated PCNA alleviates replication stress and preserves genomic integrity independently of BRCA2. Issue 1 (December 2017) - Porro, Antonio; Berti, Matteo; Pizzolato, Julia; Bologna, Serena; Kaden, Svenja; Saxer, Anja; Ma, Yue; Nagasawa, Kazuo; Sartori, Alessandro; Jiricny, Josef
The financial support for this Article was not fully acknowledged. The Acknowledgements should have included the following: This study was in part supported by the Swiss National Foundation Grant No.: 31003A-156023 to Alessandro Sartori.